2003
DOI: 10.1046/j.1523-1747.2003.12124.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variants of Drug Metabolizing Enzymes as Risk Factors in Psoriasis

Abstract: The onset or exacerbation of psoriasis, a T-cell-dependent skin disease with autoimmune features, can be triggered by drugs such as antimalarials and beta-blockers. Xenobiotics may also play a role in idiopathic psoriasis. It has been hypothesized that different metabolic efficiencies caused by variant alleles of xenobiotic metabolizing enzymes could lead to the accumulation of xenobiotics or their reactive metabolites in target organs. Subsequently, neoantigens or cryptic peptides could be presented and initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…The majority of all patients suffered from early onset of psoriasis. 2 This finding might indicate again that gene effects can be assimilated by the environment or simply by age. Owing to a recombination hot spot, a second independent Genotyping analyses were carried out by using the MassARRAY system (Sequenom, San Diego, CA, USA).…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…The majority of all patients suffered from early onset of psoriasis. 2 This finding might indicate again that gene effects can be assimilated by the environment or simply by age. Owing to a recombination hot spot, a second independent Genotyping analyses were carried out by using the MassARRAY system (Sequenom, San Diego, CA, USA).…”
mentioning
confidence: 96%
“…2 In short, 50% of the psoriasis cases were female, mean age was 48.5 years with a range of 11-84 years. Controls were slightly younger (45.7 years).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Epidemiologic studies of psoriasis had suggested a potential role for several environmental exposures, including tobacco consumption, alcohol, infections and medications, however the results were anecdotal and inconclusive. Richter-Hintz et al conducted a case-control association study for a panel of polymorphisms among xenobiotic metabolizing enzymes [31]. The results suggested that a common (hypoactive) CYP1A1 variant conferred disease susceptibility.…”
Section: Modeling Interactionsmentioning
confidence: 99%